Impact of zinc oxide, benzoic acid and probiotics on the performance and cecal microbiota of piglets - Silva, Caio Abercio da; Teixeira Bentin, Leonardo Aparecido [UNESP]; Dias, Cleandro Pazinato; Callegari, Marco Aurelio; Facina, Vitor Barbosa; Falleiros Dias, Francine Taniguchi; Passos, Adsos; Silva Martins, Claudia Cassimira da; Costa, Marcio Carvalho (Bmc, 2021)
Background Intestinal health remains a key factor in animal production because it is essential for digestion, absorption and bacterial fermentation. Feed additives have been used to attenuate the weaning stress such as Zinc Oxide (ZnO) and benzoic acid (C7H6O2). The objective of this study was to evaluate the impact of of benzoic acid and probiotics (BA + P) on performance, diarrhea and cecal microbiota of piglets in the nursery phase (23 to 65 days). Results One hundred and sixty weaned piglets with an initial weight of 6.335 +/- 0.698 kg and 23 days of age were submitted to four treatments: supplementation with 2500 ppm of Zinc oxide (ZnO), supplementation with a commercial blend of benzoic acid and probiotics (Bacillus licheniformis, Bacillus subtilis and Enterococcus faecium NCIMB 10415; Vevogut P (R)) (BA + P), supplementation with Zinc oxide plus benzoic acid and probiotics (ZnO + BA + P), and controls receiving only the basal diet without any supplementation. At 65 days of age, 32 piglets (n = 8 per treatment) were slaughtered for the evaluation of the cecal microbiota. Supplementation with ZnO and BA + P were associated with better feed conversion (P < 0.05) in the early stage (23 to 49 days) and with an improvement in all performance parameters over the entire experimental period. The occurrence of diarrhea was lower (P < 0.05) in the BA + P group. The 4 most abundant phyla along with unclassified bacteria represented 93% of all sequences. Firmicutes dominated the cecal microbiota of all groups, followed by Bacteroidetes. Richness represented by the observed number of genera and by the Chao index were statistically lower in ZnO and ZnO + BA + P supplemented animals compared to controls. The beta diversity analysis that compares similarities between bacterial communities demonstrated formation of two distinct clusters containing samples with and without supplementation with ZnO, confirming a strong influence of ZnO on the intestinal microbiota. Conclusion The use of Benzoic acid with probiotics yields similar performance results with lower impact on the gut microbiota compared to ZnO, and it should be considered as a potential alternative in swine production.
Keywords: Antibiotics; Diarrhea; Organic acids; Swine